Factors Affecting the Profitability of Non-Life Insurance Companies in Nepal - Subedi, Utsab (Nepalese Journal of Business, 2024)
This study examines the determinants of profitability of Nepalese insurance companies. Return on assets and return on equity are the dependent variables. The selected independent variables are firm size, liquidity, age of firms, financial leverage, growth rate of premiums, and volume of capital. The study is based on secondary data of 13 insurance companies with 104 observations for the study period from 2013/14 to 2020/21. The data were collected from the annual reports of Rastriya Beema Authority, reports published by Ministry of Finance and annual reports of selected Nepalese insurance companies. The regression models are estimated to test the significance and effect of firm specific factors on the profitability of Nepalese non-life insurance companies. The study showed that liquidity ratio has a negative impact on return on assets and return on equity. It means that increase in liquidity ratio leads to decrease in return on assets and return on equity. In addition, volume of capital has a positive impact on return on assets and return on equity. It shows that higher the volume of capital, higher would be the return on assets and return on equity. Similarly, firm size has a positive impact on return on assets and return on equity. It shows that larger the firm size, higher would be the return on assets and return on equity. Furthermore, firm age has a positive impact on return on assets and return on equity. It means that increase in the age of the firms leads to increase in the return on assets and return on equity. Likewise, premium growth rate has a positive impact on return on assets and return on equity. It means that higher the premium growth rate, higher would be the return on assets and return on equity. In contrast, leverage ratio has the negative impact on return on assets. It indicates that higher the leverage ratio, lower would be the return on assets and return on equity.